Leukocytoclastic Vasculitic Rash Following Second Dose of Moderna COVID-19 Vaccine - Branden Ireifej MD; Mark Weingarten BA; Umaima Dhamrah MD; Michael Weingarten MD; Suhail Hadi MD (SAGE Publishing, 2022)
The immunization against coronavirus disease (COVID-19) via vaccination serves as a significant milestone in the fight against the pandemic. Rapid introduction of various COVID-19 vaccines to stem the spread of virus has researchers scrambling to document the adverse effects left in its wake. Thus far, there have been singular examples of cutaneous vasculitis associated with COVID-19. A history of vasculitis leaves little error to miss its inclusion in diagnostic differentials. It also invokes the physiologic possibility that afflicted patients possess a more susceptible landscape for recurrence that was then triggered by the vaccine when compared with those who lack similar history. In our case report, we build on those findings with one of the first documented examples of vaccination-induced vasculitic rash in a previously asymptomatic patient.